DETERMINANT FACTORS OF FIRM VALUES IN MANUFACTURING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE (IDX) WITH FIRM SIZE AS MODERATING VARIABLE - Fitria, Amira (Asosiasi Dosen Akuntansi Indonesia, 2020)
This study aims to analyse Firm Growth, Managerial Ownership, Profitability and Capital Structure on Firm Value in Manufacturing Companies listed on the Indonesia Stock Exchange with Firm Size as a Moderating Variable. This type of research in this research is causal comparative. The population of this study is Manufacturing Companies listed on the Indonesia Stock Exchange in 2015-2017. The sample selection method uses a purposive sampling technique, so the number of samples used is 34 sample data. The data collection method used is documentation technique. Methods of data analysis using multiple linear regression methods, the absolute difference test with a significance value of 5%, and using SPSS software tools. The results showed that company growth had a significant positive effect on firm value, managerial ownership had no significant negative effect on firm value, profitability had a significant positive effect on firm value, capital structure had a significant negative effect on firm value, and firm size was unable to moderate firm growth, managerial ownership, profitability and capital structure on firm value.